RECENT NANOCOCHLEATE DRUG DELIVERY SYSTEM FOR CANCER TREATMENT: A REVIEW - NAYEK, SUJIT; VENKATACHALAM, ABHIRAMI; CHOUDHURY, SANGEETA (International Journal of Current Pharmaceutical Research, 2019)
Nanocochleates are at the forefront of the fast-growing nanotechnology sector in the delivery of drugs for cancer. This nanotechnology is the use of the cationic and anionic encapsulated drug that has poor oral bioavailability. Nanocochleate is a lipid-based drug delivery in the liposomal vesicles that is converted by calcium divalent cation into nanocochleate. Nanocochleates technology use encapsulations of the anticancer agent, which have low solubility, oral bioavailability and low permeability. This paper shows and provides an overview of the benefits of nanocochleates, drug delivery mechanism, choice of prevalent components (Phospholipids and Cations), various ways of producing nanocochleates and nanocochleate stability. Nanocochleates have far fewer constraints than other traditional carriers. To characterize nanocochleates, the suitable analytical methods are required. Therefore, in the therapy of cancer, nanocochleate becomes commonly applied and more prospective drug delivery system.